Endogenous Pain Modulation Induced by Extrinsic and Intrinsic Psychological Threat in Healthy Individuals - Gibson, W.; Moss, P.; Cheng, T.; Garnier, A.; Wright, Tony; Wand, B. (Churchill Livingstone, 2017)
© 2017 The American Pain Society. Many factors interact to influence threat perception and the subsequent experience of pain. This study investigated the effect of observing pain (extrinsic threat) and intrinsic threat of pain to oneself on pressure pain threshold (PPT). Forty socially connected pairs of healthy volunteers were threat-primed and randomly allocated to experimental or control roles. An experimental pain modulation paradigm was applied, with non-nociceptive threat cues used as conditioning stimuli. In substudy 1, the extrinsic threat to the experimental participant was observation of the control partner in pain. The control participant underwent hand immersion in noxious and non-noxious water baths in randomized order. Change in the observing participant's PPT from baseline to mid- and postimmersion was calculated. A significant interaction was found for PPT between conditions and test time (F 2,78 = 24.9, P < .005). PPT increased by 23.6% ± 19.3% between baseline and during hand immersion (F 1,39 = 43.7, P < .005). Substudy 2 investigated threat of imminent pain to self. After a 15-minute break, the experimental participant's PPT was retested ("baseline 2"). Threat was primed by suggestion of whole arm immersion in an icier, larger water bath. PPT was tested immediately before anticipated arm immersion, after which the experiment ended. A significant increase in PPT between "baseline 2" and "pre-immersion" was seen (t = -7.6, P = .005), a pain modulatory effect of 25.8 ± 20.7%. Extrinsic and intrinsic threat of pain, in the absence of any afferent input therefore influences pain modulation. This may need to be considered in studies that use noxious afferent input with populations who show dysfunctional pain modulation. Perspectives: The effect on endogenous analgesia of observing another's pain and of threat of pain to oneself was investigated. Extrinsic as well as intrinsic threat cues, in the absence of any afferent input, increased pain thresholds, suggesting that mere threat of pain may initiate analgesic effects in traditional noxious experimental paradigms.